AN EPIGENETIC CLOCK FOR AGING AND LIFE EXPECTANCY. (11th November 2018) - Levine, M; Lu, A; Quach, A; Chen, B; Baccarelli, A; Whitsel, E; Ferrucci, L; Horvath, S
Abstract: While the first generation of epigenetic biomarkers of aging were developed using chronological age as a surrogate for biological age, we hypothesize that incorporation of clinical measures of "phenotypic age" may facilitate the development of a more powerful epigenetic biomarker of aging. Results show that our newly developed epigenetic biomarker of aging strongly outperforms previous measures, in regards to predictions for a variety of aging outcomes-all-cause mortality, cancers, physical functioning, and Alzheimer's disease. Additionally, while this biomarker was developed using data from whole blood, it strongly predicts age in every tissue and cell tested. Finally, transcriptional analysis points to the potential role of interferon signaling, transcriptional machinery, and DNA damage signaling. Overall, this single epigenetic biomarker of aging is able to capture risks for an array of diverse outcomes across multiple tissues and cells, and may facilitate the development of interventions aimed at increasing healthy life expectancy.